The road not taken: Gender gaps along paths to political power - Iyer, L; Mani, A (Elsevier, 2019)
Using an original survey conducted in India’s largest state, we offer systematic evidence on the gender gaps in a rich set of electoral and non-electoral participation metrics. We find that gender gaps in non-electoral forms of participation (such as involvement in public petitions, interactions with public officials and attendance of village meetings) are larger than those in election-related activities, including political candidacy. These gender gaps in political participation persist even after we account for women’s poorer knowledge of political institutions, self-assessment of leadership skills, literacy rates and asset ownership, as well as constraints on their mobility and voice in household decisions. Using a Oaxaca-Blinder decomposition approach, we find that bringing women on par with men on these attributes would bridge less than half of the gender gap in political participation. This suggests that external factors, such as the roles played by voters, political parties or societal groups, may constitute important barriers to women’s political participation. The presence of a woman leader in the village increases women’s propensity to meet with government officials, but is not enough to close the gender gap in this outcome or others. Our evidence points to the need to consider a wider set of policy tools beyond quotas to encourage women’s civic and political engagement.